2018
DOI: 10.1016/j.marpolbul.2018.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative feeding rates of native and invasive ascidians

Abstract: Ascidians have a recent history of species introductions globally, often with strong ecological impacts. Comparisons of per capita effects of invaders and comparable natives are useful to assess such impacts. Here, we explore ingestion rates (IR) and clearance rates (CR) of Ciona intestinalis and Ciona robusta, co-occurring native and non-native ascidians, respectively, from Brittany, France. IR was positively related to food concentration, with the invader responding more strongly to increasing food concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Similarly, investigations 44 indicated that ingestion rates increased linearly with food concentration in another tunicate (Halocynthia pyriformis). However, other studies 35 did not detect a clear maximum in the feeding rates of tunicates, according to the concentrations of particles. In our case, when cultures were managed at higher doses (ad libitum) residual suspended particles were still present before water changes, demonstrating that individuals never starved.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similarly, investigations 44 indicated that ingestion rates increased linearly with food concentration in another tunicate (Halocynthia pyriformis). However, other studies 35 did not detect a clear maximum in the feeding rates of tunicates, according to the concentrations of particles. In our case, when cultures were managed at higher doses (ad libitum) residual suspended particles were still present before water changes, demonstrating that individuals never starved.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, the diet Shellfish produced sufficient growth and survival rates, especially at higher concentrations, but also led to an increase in nitrates and phosphates that the automatic system hardly controlled during the second half of the experiment. The automatic system performed at its best when feed doses were lower and produced acceptable results, at higher concentrations, in the treatment Compound, evidently promoting lower pollution of water, although most chemical and physical parameters were kept in the range preferred by this species 35 . Particle concentrations tested in this study represent sub-threshold levels for most tunicates, because negative effects of particle additions would be expected at concentration greater than 46 mg l −1 according to previous investigations 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative functional response approach ( Fig. 1), whereby the impacts of invasive species are compared with analogous native species as eco-evolutionary baselines (Dick et al 2017c), have proved a reliable tool for explaining the ecological effects of existing invasive species and predicting the impacts of new, emerging and indeed potential future invaders under a wealth of different contexts (Dick et al 2014, b, c, Crookes et al 2018, Howard et al 2018, Hoxha et al 2018. Such contexts include dissolved oxygen levels (Laverty et al 2015a), habitat complexity (Wasserman et al 2016), temperature regimes (Zamani et al 2006), water chemistry gradients (Kestrup et al 2011), higher order predators (Barrios-O'Neill et al 2014) and parasites (Laverty et al 2017b).…”
Section: Background and Development Of Invasive Species Ecological Immentioning
confidence: 99%
“…Three types of FR have been described. A Type I response is characterised by a lack of handling time, where consumption rate increases linearly as resource density rises (Jeschke et al 2014;Hoxha et al 2018). Hyperbolic Type II responses are characterised by high proportional consumption at low resource densities followed by an asymptote, and are widely regarded as destabilising on resource populations, such as prey species that cannot escape predation when relatively rare (Murdoch and Oaten 1975;Hassell 1978).…”
Section: Introductionmentioning
confidence: 99%